AKURASI ARAH KIBLAT MASJID DI KELURAHAN ALLIRITENGAE KECAMATAN TURIKALE KABUPATEN MAROS - Nurlinda Sari Abdul Rauf; Supardin Supardin (HISABUNA: Jurnal Ilmu Falak, 2020)
It is a fact that the direction of the mosque located in our country still differs from one another, the direction of the spread of the mosque in the community still differs to 20 degrees or beyond. Qibla deviation is most commonly found in the amount of 25⁰ which is right to the West.  How far the deviation that occurs if wrong in determining the position of the Qibla direction leading to the ka’ba in Mecca, where the distance from the regency of Maros is as far as 9156.24 km. then if there is an error of just 1⁰, then there is a deviation as far 110 km. This study has the main problem regarding the accuracy of the position of the qibla directionof mosquesin the Village of Alliritengae, Turikale sub-District, Maros District with the type of research is a descriptive qualitative research that is a type of research that describes qualitatively about objects discussed according to the reality that can be found in the community. The conclusion in this study is that the determination of the direction of qibla is a test given by Allah Almighty to His servants to test how much their faith in trying to perfect their servitude to Allah Almighty. Therefore, it is expected that all Muslims in Indonesia should try to perfect our worship of Allah Almighty, especially in justifying the direction of qibla when we want to pray.